Software Architecture Requirements for Procedural Content Generation in Digital Games: A Systematic Mapping - So, Arthur R. Pinheiro; Souza, Francisco Carlos M.; Souza, Alinne C. Corrêa; Fabri, José Augusto (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Procedural Content Generation (PCG) has become essential in game development to support designers and manage growing system complexity. However, there is a lack of dedicated software architectures for PCG-based systems. Objective: In this study, we aim to identify and analyze software architectures and frameworks used in games that employ PCG techniques. Methodology: A systematic mapping study reviewed 121 publications. From these, we selected nine studies—four through database search, three via snowballing, and two from manual search. Results: Most architectures support multi-content generation and integrate user experience metrics. Standard components include data storage, multi-source inputs, and modular generators. The selected studies highlight trends toward modular, scalable, and user-centered architectures for PCG, offering a foundation for future research and development in this domain.